Moral Values in the Film Not One Less《一个都不能少》 张艺谋对《一个都不能少》电影道德价值分析 - Fakhriawan Fathu Rahman; Tuty Wulandari Bin Ahmad; Syafri Badaruddin; M. Amir P.; Citra Andini (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The objective of this research is to examine the form of moral values and to explain what are the moral values of the main character, namely Wei Minzhi in the film "Not One Less" 《一个都不能少》Yígè dōu bùnéng shǎo Director Zhang Yimou. This research used descriptive qualitative method. Data collection was carried out by watching, listening, taking notes, and classifying moral values in the film “Not One Less” 《一个都不能少》Yígè dōu bùnéng shǎo Director Zhang Yimou. Based on the results of an analysis of the moral values contained in the film “Not One Less” 《一个都不能少》Yígè dōu bùnéng shǎo Director Zhang Yimou, there are two types: 1) the good moral values displayed by the protagonist, namely social care, self-sacrifice and enthusiasm never give up. 2) the bad moral values displayed by the antagonist are disrespect, not admitting mistakes, irresponsibility and lying. The moral values contained in the main character, namely Wei Minzhi, are based on Suseno's moral values, namely honesty, being yourself, willingness to take responsibility, moral independence, moral courage, humility.